PENGARUH TERAPI BERMAIN ORIGAMI PADA ANAK USIA TODDLER YANG MENGALAMI KECEMASAN AKIBAT HOSPITALISASI DIRUANG ASTER RSUD Prof. Dr. MARGONO SOEKARJO PURWOKERTO - Nur Anggun Puspita; Atun Raudotul Ma’rifah; Susio Maryati (Universitas Harapan Bangsa Purwokerto, 2016)
Backgriund: Playing is a voluntary activity to obtain pleasure / satisfaction. Origamican be used to teach skills in preschool children because the movement of folding papercan develop both creativity and motor neuron system. Objective : The purpose of this study was to reveal The effect of origami playing therapy on toddlers experiencing childhood anxiety due to hospitalization in aster ward Prof. Dr. Margono Soekarjo hospital Purwokerto 2015.Method : This research method is pre-experimental with pretest-posttest design. Thepopulation of this study were all children toddler (1-3 years old) in Aster Ward Prof.Dr. Margono Soekarjo Purwokerto. The sampling method used Nonprobabilitysampling with Accidental sampling. There were 17 respondents taken as the sample.Result : Statistical test results obtained with the Wilcoxon test were significant value p0.003 (p value <α) and the value of z count -2.972, which means there is the effect oforigami origami playing therapy anxiety due to hospitalization. Conclusion : In conclusion , there is The effect of origami playing therapy on toddlers experiencing childhood anxiety due to hospitalization in aster ward Prof. Dr. MargonoSoekarjo hospital Purwokerto. Keywords: Origami, Child toddler, Anxiety, Hospitalization.